Sensory Characteristics of Jelly Candy with The Addition of Tamarind Tumeric : Karakteristik Sensoris Permen Jeli dengan Penambahan Kunyit Asam - Melati, Denis; Sukha, Aulia Rohma; Anggara, Junica Happy Dwi Ananda Budi; Purwitasari, Nyeni; Maharani, Pepsi; Zahroh, Ummu (Universitas Muhammadiyah Sidoarjo, 2024)
Abstract. Technological developments have an impact on people's awareness of the importance of maintaining a healthy body by optimizing natural resources as functional food. Functional food is food and drink that is often consumed by the public because it contains bioactive compounds that are beneficial for health. Gummy candy is a type of jelly-like soft candy made from a mixture of sugar and the purpose of this study was to determine the acceptability of gummy candies with the addition of turmeric and tamarind as functional foods. This study used an experimental method with organoleptic tests on the resulting functional food products. There were 3 treatments in this study namely P1 (100% mineral water: 0% sour turmeric), P2 (81.5% mineral water: 18.5% sour turmeric) and P3 (63% mineral water: 37% sour turmeric). Based on the Friedman rank test, and carried out with the Wilcoxon test, it was found that the tamarind turmeric substitution had a significant effect on the color and texture parameters with a value (p = 0.00), but was not significantly different in the aroma parameter with a value (p = 0.81) and taste with a value (p = 0.16) on organoleptic gummy candy. It can be concluded that P3 got superior scores compared to P1 and P2 on the color and aroma parameters, while P1 excelled on the texture and taste parameters. The addition of tamarind turmeric will affect the organoleptic acceptability of Gummy candies.